Targeting neurolysin in acute myeloid leukemia - Mirali, Sara (Mol Cell Oncol, 2020)
We recently identified the mitochondrial peptidase, neurolysin (NLN), as a top hit in an acute myeloid leukemia (AML) viability screen. Using chemical and genetic approaches, we demonstrated that loss of NLN disrupted respiratory chain supercomplex assembly and impaired oxidative metabolism in AML. Moreover, inhibition of NLN in vitro and in vivo reduced the growth of AML cells.